The multiple forms of racism and the challenges it poses to higher education systems - Mato, Daniel Alejandro (2020)
Racism is an ideology according to which human beings are classifiable into "races" and some of them are "superior" to others. This ideology is not only expressed and exercised through "visible" social practices, which is what the application of the expression "racial discrimination" is usually limited. It also operates through disadvantages accumulated over centuries, the existence of which has been "naturalized". These disadvantages are the result of inequities and forms of inequality and exclusion of an economic, political, and socio-cultural nature, which are reproduced and multiplied through both prejudices and forms of "common sense", as well as institutional norms, devices, and practices. The idea of ​​"structural racism" is useful for referring to this set of factors in a comprehensive way. However, it is analytically insufficient in serving as a basis for the design of concrete intervention initiatives that are potentially effective in eradicating racism from Higher Education systems. This article seeks to contribute to the analysis of the different ways in which racism operates in Higher Education systems and the challenges it poses.